Lead acid battery
By adding barium sulfate and organic anti-shrinkage agent to the negative electrode material of the lead-acid battery, the problem that the battery is difficult to take into account in both high-rate discharge and low-temperature and high-rate discharge performance is achieved, and the battery performance is comprehensively improved.
Patent Information
- Application Number
- JP2020197581
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-11-27
AI Technical Summary
The existing lead-acid batteries have problems that are difficult to take into account in terms of high-rate discharge performance and low-temperature and high-rate discharge performance, and it is difficult to achieve both high-levels at the same time.
BaSO4 with a specific surface area and a condensate containing a bisphenol unit are added to the negative electrode battery material, and the average particle size and content of barium sulfate are controlled to improve the battery's high-rate discharge and charging acceptance performance.
The lead-acid battery has been improved in terms of high-rate discharge and low-temperature and high-rate discharge performance, while improving the charging acceptance performance of the battery.
Smart Images

Figure 0007647070000002 
Figure 0007647070000003 
Figure 0007647070000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a lead-acid battery. [Background technology]
[0002] Lead-acid batteries are used in various applications, including automotive and industrial use. A lead-acid battery usually includes a negative electrode plate, a positive electrode plate, a separator (or mat), and an electrolyte. Each electrode plate includes a current collector and an electrode material. In order to impart various functions, various additives are added to the electrode material.
[0003] Patent Document 1 (JP Patent Publication No. 2012-043594) discloses "a negative electrode plate for a lead-acid battery, the negative electrode active material of which contains, as essential components, barium sulfate, lignin, a salt of naphthalenesulfonic acid-formaldehyde condensate, and a bisphenol-sulfonic acid-formaldehyde condensate" (Claim 1).
[0004] Patent Document 2 (JP Patent Publication 10-040906 A) discloses "a negative electrode plate for a sealed lead-acid battery, in which a refiner powder made of MSO4 (e.g. BaSO4) having the same crystal form as the discharge product of the negative electrode active material and capable of becoming a crystal nucleus is contained in a negative electrode active material layer, characterized in that the refiner powder is a powder in which the ratio S2 / S1 of the value S1 obtained by multiplying the surface area of a sphere calculated using a median diameter determined by a laser diffraction particle size distribution measurement method by the number of powder particles and the total surface area S2 of the entire refiner powder determined by a BET method is 2.2 or less."
[0005] Patent Document 3 (WO 2018 / 100639) discloses "a lead-acid battery comprising a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode has a negative electrode material including a chemically treated mixture containing a raw material for a negative electrode active material and particles containing barium (such as barium sulfate), the particles having an average primary particle size of 0.10 μm or less before chemical treatment, and the electrolyte containing sodium ions." [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2012-043594 A [Patent Document 2] Japanese Patent Application Publication No. 10-040906 [Patent Document 3] International Publication No. 2018 / 100639 Summary of the Invention [Problem to be solved by the invention]
[0007] There is a demand for improvement in various characteristics of lead-acid batteries. For example, high high-rate discharge performance (especially high-rate discharge performance at low temperatures) and high charge acceptance performance are required for lead-acid batteries. It is difficult to achieve both of these at a high level. [Means for solving the problem]
[0008] One aspect of the present invention relates to a lead-acid battery including a negative electrode containing a negative electrode material and a positive electrode, the negative electrode material containing an organic shrinkage preventer and barium sulfate, the organic shrinkage preventer being a condensate containing a bisphenol unit, and the barium sulfate having a surface area of 0.04 m per 1 g of the negative electrode material. 2 That's all. Effect of the Invention
[0009] According to the present invention, a lead-acid battery having both high high-rate discharge performance and high charge acceptance performance can be obtained. [Brief description of the drawings]
[0010] [Figure 1] 1 is a partially cutaway exploded perspective view showing the appearance and internal structure of a lead-acid battery according to one aspect of the present invention. FIG. [Diagram 2]1 is a graph showing an example of the relationship between the surface area (Z) of barium sulfate particles and low-temperature high-rate discharge performance. [Diagram 3] 1 is a graph showing an example of the relationship between the surface area (Z) of barium sulfate particles and charge acceptance performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the following, the embodiment of the present invention will be described with examples, but the present invention is not limited to the examples described below. In the following description, specific numerical values and materials may be exemplified, but other numerical values and materials may be applied as long as the effects of the present invention can be obtained. In this specification, when "numerical value A to numerical value B" is mentioned, the range includes numerical value A and numerical value B.
[0012] (lead acid battery) The lead-acid battery according to this embodiment includes a negative electrode containing a negative electrode material, and a positive electrode. The negative electrode material contains an organic shrinkage preventer and barium sulfate. The organic shrinkage preventer is a condensate containing a bisphenol unit. Hereinafter, the organic shrinkage preventer may be referred to as "organic shrinkage preventer (B)". The surface area of barium sulfate is 0.04 m per 1 g of the negative electrode material. 2 That is all. Hereinafter, the surface area of barium sulfate per 1 g of the negative electrode material may be referred to as "surface area (Z)". In a typical example of the lead-acid battery according to this embodiment, the barium sulfate in the negative electrode material can be considered to exist in the form of particles, so barium sulfate can be read as barium sulfate particles.
[0013] It is known that the characteristics of a lead-acid battery are improved by adding barium sulfate to the negative electrode material. The added barium sulfate acts as a nucleus for lead sulfate generated during discharge, resulting in the generation of fine lead sulfate. Therefore, lead sulfate is more likely to be generated during discharge. In addition, since the generated lead sulfate is fine, it is easier for the lead sulfate to dissolve during charging. It is believed that these reasons improve the characteristics of the lead-acid battery. However, as a result of investigation, the present inventors have newly found that the effect of adding barium sulfate differs depending on the type of organic shrinkage inhibitor added to the negative electrode material. As a result of further investigation, the present inventors have found that there is a specific relationship between the type of organic shrinkage inhibitor and the conditions for adding barium sulfate, and the characteristics of the lead-acid battery. The present invention is an invention based on this new finding.
[0014] According to the configuration of this embodiment, a lead-acid battery having both high high-rate discharge performance and high charge acceptance performance is obtained. The reason why this effect is obtained is not clear at present, but it can be considered as follows. When the surface of barium sulfate is covered with an organic shrinkage inhibitor, the effect of adding barium sulfate is reduced. From various studies, it was found that the area where the organic shrinkage inhibitor (B) covers the negative electrode active material or additives may be larger than the area where the same amount of lignin compound covers the negative electrode active material or additives. Therefore, when the organic shrinkage inhibitor (B) is used as the organic shrinkage inhibitor, it is considered necessary to add barium sulfate to the negative electrode material so that it has a surface area (Z) of a predetermined value or more.
[0015] Bisphenol is a compound having two hydroxyphenyl groups. A bisphenol unit is a unit derived from bisphenol among the units constituting a condensation product. The condensation product is obtained by condensing a plurality of compounds including bisphenol. Hereinafter, bisphenol may be referred to as a "bisphenol compound."
[0016] The surface area (Z) of barium sulfate per 1 g of negative electrode material is 0.04 m 2 Above 0.05m 2The upper limit of the surface area (Z) is not particularly limited and is up to 0.15 m 2 Below, 0.09m 2 Less than or equal to 0.07m 2 The surface area may be less than 0.15 m 2 By setting the surface area (Z) at or below 0.04 m, it is possible to suppress adverse effects caused by an excessively high content of barium sulfate (for example, a decrease in the binding strength between lead particles (active material)). These lower and upper limits can be combined in any combination as long as there is no contradiction. For example, the surface area (Z) is 0.04 m 2 ~0.15m 2 Range: 0.04m 2 ~0.09m 2 Range: 0.04m 2 ~0.07m 2 Range: 0.05m 2 ~0.15m 2 Range: 0.05m 2 ~0.09m 2 Range: 0.05m 2 ~0.07m 2 It may be in the range.
[0017] The surface area (Z) of barium sulfate per 1 g of the negative electrode material can be adjusted, for example, by changing at least one of the amount of barium sulfate added and the particle size of barium sulfate. For example, the surface area (Z) can be increased by increasing the amount of barium sulfate added. Also, when the amount of barium sulfate added is the same, the smaller the particle size of barium sulfate, the larger the surface area (Z).
[0018] The average particle size of barium sulfate may be 0.5 μm or more and 1.0 μm or less. The average particle size of barium sulfate may be 0.5 μm or more and 0.8 μm or less, or 0.8 μm or more and 1.0 μm or less. By making the average particle size of barium sulfate 0.5 μm or more, it is possible to suppress the outflow of barium sulfate. By making the average particle size of barium sulfate 1.0 μm or less, it is possible to increase the surface area (Z) of barium sulfate with a small amount of addition.
[0019] The average particle size of barium sulfate in the negative electrode material can be adjusted, for example, by changing the particle size of barium sulfate particles added when preparing the negative electrode plate. Barium sulfate particles with various particle sizes are commercially available, so the particle size of the barium sulfate particles to be added can be easily controlled by using them.
[0020] The content of barium sulfate in the negative electrode material may be 0.9% by mass or more. By setting the content to 0.9% by mass or more, it is possible to achieve both high-rate discharge performance and charge acceptance performance at a particularly high level. The content may be 0.5% by mass or more, 0.9% by mass or more, 1.2% by mass or more, 1.5% by mass or more, or 1.8% by mass or more. The upper limit of the content is not particularly limited, and may be, for example, 3.2% by mass or less, 2.8% by mass or less, 2.4% by mass or less, or 2.1% by mass or less. These lower and upper limits can be arbitrarily combined as long as there is no contradiction. For example, the content may be in the range of 0.5 to 3.2% by mass, 0.9 to 2.8% by mass, 1.2 to 2.8% by mass, 1.5 to 2.8% by mass, 0.9 to 2.4% by mass, or 0.9 to 2.1% by mass.
[0021] The surface area (Z), average particle size, and content of barium sulfate in the negative electrode material are measured by the methods described below. That is, they are values measured by the methods described below.
[0022] Examples of the bisphenol unit include a bisphenol A unit, a bisphenol S unit, and a bisphenol F unit. The organic shrink-proofing agent (B) may be a condensate containing at least one unit selected from the group consisting of a bisphenol A unit, a bisphenol S unit, and a bisphenol F unit. For example, the organic shrink-proofing agent (B) may contain a bisphenol A unit, a bisphenol S unit, a bisphenol F unit, or two or three units selected therefrom. For example, the organic shrink-proofing agent (B) may be a condensate containing a bisphenol S unit and a bisphenol A unit. The bisphenol A unit, the bisphenol S unit, and the bisphenol F unit are units derived from bisphenol A, bisphenol S, and bisphenol F, respectively.
[0023] The organic shrink-resisting agent (B) may contain other units in addition to the bisphenol unit. Examples of the other units include a phenolsulfonic acid unit.
[0024] The organic shrink-preventing agent (B) can be obtained, for example, by condensing the compound from which the above unit is derived with another compound. Examples of the other compound include aldehyde compounds (e.g., formaldehyde), sodium sulfite, etc. The organic shrink-preventing agent (B) may be a commercially available one, or may be synthesized based on a known synthesis method. Specific examples of the organic shrink-preventing agent (B) will be described later.
[0025] The organic shrink-proofing agent (B) may be synthesized by reacting a bisphenol with an aldehyde compound. Here, the reaction between the bisphenol and the aldehyde compound may be carried out in the presence of a sulfite, or a bisphenol containing a sulfur element (e.g., bisphenol S) may be used to obtain an organic shrink-proofing agent (B) containing a sulfur element. The bisphenol to be condensed to obtain the organic shrink-proofing agent (B) may be one type or two or more types. The aldehyde compound may be an aldehyde (e.g., formaldehyde), or a condensate (or polymer) of an aldehyde. Examples of the aldehyde condensate (or polymer) include paraformaldehyde, trioxane, and tetraoxymethylene. The aldehyde compound may be used alone or in combination of two or more types.
[0026] The bisphenol may have a sulfur-containing group. That is, the organic shrink-proofing agent (B) may contain elemental sulfur. The sulfur-containing group may be directly bonded to an aromatic ring contained in the bisphenol. Examples of the sulfur-containing group include a sulfonic acid group and a sulfonyl group. The sulfonic acid group may exist in an acid form or in a salt form such as a Na salt.
[0027] The content of the organic shrinkage inhibitor (B) contained in the negative electrode material may be 0.01% by mass or more. According to this configuration, the low-temperature high-rate discharge performance can be particularly improved. The content may be 0.05% by mass or more, 0.1% by mass or more, or 0.2% by mass or more. The content may be 1.0% by mass or less, 0.6% by mass or less, 0.4% by mass or less, or 0.2% by mass or less. These lower and upper limits can be arbitrarily combined as long as there is no contradiction. For example, the content may be in the range of 0.01 to 1.0% by mass, the range of 0.05 to 0.4% by mass, the range of 0.05 to 0.2% by mass, or the range of 0.1 to 0.2% by mass.
[0028] The negative electrode material may or may not contain other organic shrink-preventing agents than the organic shrink-preventing agent (B). Examples of such other organic shrink-preventing agents will be described later. However, in order to suppress adverse effects caused by an increase in the amount of the organic shrink-preventing agent, the content (mass basis) of the other organic shrink-preventing agent in the negative electrode material is preferably less than the content of the organic shrink-preventing agent (B) in the negative electrode material. For example, the content (mass basis) of the other organic shrink-preventing agent in the negative electrode material may be in the range of 0 to 0.9 times (for example, in the range of 0 to 0.5 times, in the range of 0 to 0.3 times, or in the range of 0 to 0.1 times) the content of the organic shrink-preventing agent (B) in the negative electrode material.
[0029] A preferred example of the negative electrode material satisfies the following condition (1) and further satisfies the following conditions (2) and / or (3). This example may further satisfy the following conditions (4) and / or (5). (1) The surface area (Z) of barium sulfate per gram of negative electrode material is 0.04 m 2 or more than 0.05m 2 That is all. The surface area (Z) may be within the above range. (2) The average particle size of the barium sulfate is 0.5 μm or more and 1.0 μm or less. The average particle size may be within the above range. (3) The content of barium sulfate in the negative electrode material is 0.9% by mass or more, for example, in the range of 0.9 to 2.8% by mass. The content may be within the above range. (4) The bisphenol unit is at least one selected from the group consisting of a bisphenol A unit, a bisphenol S unit, and a bisphenol F unit. The bisphenol unit may be a bisphenol A unit and / or a bisphenol S unit. The organic shrink-preventing agent (B) may be the above-mentioned condensation product. (5) The content of the organic shrink-preventing agent (B) contained in the negative electrode material is in the range of 0.01 to 1.0% by mass. The content may be within the above range. The content (by mass) of the organic shrink-preventing agent other than the organic shrink-preventing agent (B) in the negative electrode material may be less than the content of the organic shrink-preventing agent (B) in the negative electrode material.
[0030] The negative electrode material may further contain a predetermined polymer compound other than the organic shrinkage inhibitor (B). The polymer compound may be referred to as "polymer compound (P)" hereinafter. The content of the polymer compound (P) in the negative electrode material may be in the range of 100 ppm to 1000 ppm on a mass basis. The content may be less than 100 ppm or more than 1000 ppm. The content may be 50 ppm or more, 100 ppm or more, or 200 ppm or more. The content may be 2000 ppm or less, 1000 ppm or less, 600 ppm or less, or 400 ppm or less. These lower and upper limits may be combined arbitrarily. For example, the content may be in the range of 50 ppm to 600 ppm, 100 ppm to 600 ppm, 200 ppm to 600 ppm, or 200 ppm to 400 ppm.
[0031] The first example of the polymer compound (P) is measured using deuterated chloroform as a solvent. 1 It is a polymer compound having a peak in the range of 3.2 ppm to 3.8 ppm in the chemical shift of the H-NMR spectrum. 1 Unless otherwise specified, the H-NMR spectrum was measured using deuterated chloroform as a solvent. 2-4 It is a polymer compound containing a repeating structure of an alkylene unit. The polymer compound included in the first example of the polymer compound (P) and the polymer compound included in the second example of the polymer compound (P) overlap at least partially. The polymer compound (P) may be a commercially available product. Alternatively, the polymer compound (P) may be synthesized by a known method.
[0032] By adding the polymer compound (P) to the negative electrode material, it is possible to reduce the amount of overcharge electricity, and thereby reduce the loss of electrolyte. The reason why the polymer compound (P) can reduce the amount of overcharge electricity is as follows. The polymer compound (P) is an oxy-C2-4 Since it contains a repeating structure of alkylene units, it is easy to have a linear structure. Therefore, the polymer compound (P) added to the negative electrode material thinly and widely covers the surface of the lead in the negative electrode material. By covering the surface of the lead with the polymer compound (P), the hydrogen overvoltage increases, and as a result, the side reaction of generating hydrogen during overcharging is less likely to occur. On the other hand, if a large amount of the polymer compound (P) is added, the charge acceptance may decrease. In the present invention, a specific amount of a specific polymer compound (P) is added to the negative electrode material. This makes it possible to obtain a lead-acid battery with high charge acceptance and low electrolyte loss.
[0033] The polymer compound (P) is oxyC 2-4 It is preferable that the alkylene unit contains a repeating structure. 2-4 When a polymer compound (P) containing a repeating structure of alkylene units is used, it is believed that the polymer compound (P) is more easily adsorbed to lead and is more likely to have a linear structure, which makes it easier to thinly cover the lead surface. Therefore, the amount of overcharge electricity can be more effectively reduced and the effect of suppressing the decrease in charge acceptance can be further improved.
[0034] The lead acid battery may be either a valve regulated (sealed) lead acid battery (VRLA type lead acid battery) or a flooded (vented) lead acid battery.
[0035] In this specification, the analysis of substances in the negative electrode material (such as organic shrinkage inhibitors, polymer compounds (P), and barium sulfate) is performed using the negative electrode material of a negative plate taken out from a fully charged lead-acid battery, unless otherwise specified.
[0036] (Terminology explanation) (electrode material) The negative electrode material and the positive electrode material are usually held by a current collector. The electrode material is the portion of the electrode plate excluding the current collector. A member such as a mat or pasting paper may be attached to the electrode plate. Such a member (also called an attachment member) is used integrally with the electrode plate and is therefore included in the electrode plate. When the electrode plate includes an attachment member (such as a mat or pasting paper), the electrode material is the portion of the electrode plate excluding the current collector and the attachment member.
[0037] (Polymer Compound (P)) The polymer compound (P) satisfies at least one of the following conditions (i) and (ii). Condition (i) Polymer compounds (P) are measured using deuterated chloroform as a solvent. 1 In the H-NMR spectrum, it has a peak in the range of 3.2 ppm to 3.8 ppm. Condition (ii) The polymer compound (P) is oxyC 2-4 It contains a repeating structure of alkylene units.
[0038] Under condition (i), the peak in the range of 3.2 ppm to 3.8 ppm is oxy-C 2-4 It is derived from an alkylene unit. In other words, the polymer compound (P) satisfying the condition (ii) is also the polymer compound (P) satisfying the condition (i). The polymer compound (P) satisfying the condition (i) is an oxyC 2-4 The polymer compound (P) may contain a repeating structure of a monomer unit other than an alkylene unit, and may have a certain molecular weight. The number average molecular weight (Mn) of the polymer compound (P) that satisfies the above (i) or (ii) may be, for example, 300 or more.
[0039] (Oxy C 2-4 Alkylene unit) Oxy C 2-4 The alkylene unit is -OR 1 - is a unit represented by R 1 is C2-4 R represents an alkylene group (an alkylene group having 2 to 4 carbon atoms). 1 may contain alkylene groups having different numbers of carbon atoms.
[0040] (Organic shrink-proofing agent) The organic shrinkage inhibitor refers to an organic compound among compounds that have the function of suppressing the shrinkage of lead, which is the negative electrode active material, when a lead-acid battery is repeatedly charged and discharged.
[0041] (number average molecular weight) The number average molecular weight (Mn) is determined by gel permeation chromatography (GPC). The standard substance used in determining Mn is polyethylene glycol.
[0042] (Weight average molecular weight) The weight average molecular weight (Mw) is determined by GPC. The standard substance used in determining Mw is sodium polystyrene sulfonate.
[0043] (Sulfur content in organic shrink-proofing agent) The content of sulfur element in an organic shrink-preventer being X μmol / g means that the content of sulfur element contained in 1 g of the organic shrink-preventer is X μmol.
[0044] (fully charged) The fully charged state of a flooded lead-acid battery is defined by JIS D 5301:2019. More specifically, the fully charged state is defined as a state in which the lead-acid battery is charged in a water tank at 25°C ± 2°C with a current (A) 0.2 times the value (unit: Ah) listed as the rated capacity until the terminal voltage during charging or the electrolyte density converted to a temperature of 20°C shows a constant value with three significant digits three consecutive times. In addition, in the case of a valve-regulated lead-acid battery, the fully charged state is defined as a state in which constant-current constant-voltage charging of 2.23 V / cell is performed in an air tank at 25°C ± 2°C with a current (A) 0.2 times the value (unit: Ah) listed as the rated capacity, and charging is terminated when the charging current during constant-voltage charging becomes 0.005 times the value (unit: Ah) listed as the rated capacity.
[0045] A fully charged lead-acid battery refers to a lead-acid battery that has already been chemically formed and is fully charged. A lead-acid battery may be fully charged immediately after chemical formation, or after a period of time has passed since chemical formation (for example, a lead-acid battery that has been in use (preferably in the early stages of use) after chemical formation may be fully charged). An early stage battery refers to a battery that has not been in use for very long and has hardly deteriorated at all.
[0046] (Top and bottom directions of lead-acid batteries or components of lead-acid batteries) In this specification, the up-down direction of a lead-acid battery or components of the lead-acid battery (such as plates, a battery case, and a separator) refers to the up-down direction in the vertical direction of the lead-acid battery when the lead-acid battery is in use. Each of the positive and negative plates has a lug for connecting to an external terminal. In some cases, such as a horizontal valve-regulated lead-acid battery, the lug is provided on the side of the plate so as to protrude laterally, but in most lead-acid batteries, the lug is usually provided on the top of the plate so as to protrude upward.
[0047] Hereinafter, the lead-acid battery according to the embodiment of the present invention will be described in detail with respect to each of its main components, but the present invention is not limited to the following embodiment.
[0048] [Lead acid battery] (Negative plate) The negative plate includes a negative current collector and a negative electrode material supported on the negative current collector.
[0049] (Negative electrode current collector) The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the negative electrode current collector because it is easy to support the negative electrode material.
[0050] The lead alloy used for the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element. The negative electrode current collector may have a surface layer. The surface layer and the inner layer of the negative electrode current collector may have different compositions. The surface layer may be formed on a part of the negative electrode current collector. The surface layer may be formed on the ear of the negative electrode current collector. The surface layer of the ear may contain Sn or an Sn alloy.
[0051] (Negative electrode material) The negative electrode material includes an organic shrinkage inhibitor (B) and barium sulfate. The negative electrode material further includes a negative electrode active material (specifically, lead or lead sulfate) that exhibits capacity through an oxidation-reduction reaction. The negative electrode material may include at least one selected from the group consisting of carbonaceous materials and other additives. Examples of additives include, but are not limited to, organic shrinkage inhibitors, barium sulfate, and fibers (such as resin fibers). The negative electrode active material in a charged state is sponge-like lead, but an unformed negative plate is usually made using lead powder.
[0052] (Polymer Compound (P)) A first example of the polymer compound (P) is 1 In the chemical shift of the H-NMR spectrum, the peak is in the range of 3.2 ppm to 3.8 ppm. Such a polymer compound (P) is an oxyC2-4 The oxy C contained in the polymer compound (P) has an alkylene unit. 2-4 Examples of the alkylene unit include an oxyethylene unit, an oxypropylene unit, an oxytrimethylene unit, an oxy2-methyl-1,3-propylene unit, an oxy1,4-butylene unit, and an oxy1,3-butylene unit. The polymer compound (P) contains such an oxyC 2-4 The alkylene unit may have one type or two or more types.
[0053] The polymer compound (P) is oxyC 2-4 It is preferred that the repeating structure of the alkylene unit is a type of oxy C 2-4 It may contain an alkylene unit, and two or more kinds of oxy C 2-4 The polymer compound (P) may contain one type of the repeating structure or two or more types of the repeating structures.
[0054] Oxy C 2-4 The polymer compound (P) having a repeating structure of alkylene units also includes those classified as surfactants (more specifically, nonionic surfactants).
[0055] The polymer compound (P) is, for example, oxy C 2-4 Poly(C) is a hydroxy compound with repeating alkylene units. 2-4 Alkylene glycol, oxy C 2-4 Polyol polyC, a copolymer containing repeating alkylene units 2-4 Alkylene oxide adducts, ethers or esters of these hydroxy compounds. 2-4 Examples of alkylene glycols include polyethylene glycol, polypropylene glycol, and polyoxyethylene polyoxypropylene glycol.
[0056] As copolymers, different oxy C 2-4 Copolymers containing alkylene units, etc. The copolymer may be a block copolymer.
[0057] Oxy C 2-4 In a polymer compound (P) containing a repeating structure of an alkylene unit, the proportion of oxy C in all structural units is 2-4 The proportion of the alkylene unit may be in the range of 50 mol% to 100 mol%, 60 mol% to 100 mol% (for example, in the range of 75 mol% to 100 mol%), or 60 mol% to 95 mol% (for example, in the range of 75 mol% to 95 mol%). 2-4 The alkylene units may be oxyethylene units and / or oxypropylene units.
[0058] The polyol may be any of aliphatic polyols, alicyclic polyols, aromatic polyols, and heterocyclic polyols. From the viewpoint of facilitating thin spreading of the polymer compound (P) on the lead surface, aliphatic polyols and alicyclic polyols (e.g., polyhydroxycyclohexane, polyhydroxynorbornane, etc.) are preferred, and among them, aliphatic polyols are preferred. Examples of aliphatic polyols include aliphatic diols and polyols having a triol or more (e.g., glycerin, trimethylolpropane, pentaerythritol, sugar or sugar alcohol, etc.). Examples of aliphatic diols include alkylene glycols having 5 or more carbon atoms. Examples of alkylene glycols include C 5~14 Alkylene glycol or C 5-10 The sugar or sugar alcohol may be, for example, sucrose, erythritol, xylitol, mannitol, sorbitol, etc. The sugar or sugar alcohol may be either a chain structure or a cyclic structure. In the polyalkylene oxide adduct of the polyol, the alkylene oxide is the oxy C of the polymer compound (P). 2-4 Corresponding to an alkylene unit, at least C 2-4It contains an alkylene oxide. From the viewpoint that the polymer compound (P) is likely to have a linear structure, the polyol is preferably a diol.
[0059] The etherified product is the above-mentioned oxy C 2-4 At least some of the terminal -OH groups (composed of a hydrogen atom of the terminal group and an oxygen atom bonded to the hydrogen atom) of the hydroxy compound having a repeating structure of alkylene units are etherified to form -OR 2 Groups, where R 2 is an organic group.) Some or all of the terminals of the polymer compound (P) may be etherified. For example, one terminal of the main chain of the linear polymer compound (P) is an -OH group and the other terminal is an -OR group. 2 It may also be a group.
[0060] The esterified product is the above-mentioned oxy C 2-4 At least some of the terminal -OH groups (composed of a hydrogen atom of the terminal group and an oxygen atom bonded to this hydrogen atom) of a hydroxy compound having a repeating structure of an alkylene unit are esterified to form -OC(=O)-R 3 Groups, where R 3 is an organic group.) Some or all of the terminals of the polymer compound (P) may be esterified. For example, one terminal of the main chain of the linear polymer compound (P) is an -OH group and the other terminal is an -OC(=O)-R 3 It may also be a group.
[0061] organic group R 2 and R 3Each of the above groups includes a hydrocarbon group. The hydrocarbon group may have a substituent (e.g., a hydroxy group, an alkoxy group, and / or a carboxy group). The hydrocarbon group may be any of aliphatic, alicyclic, and aromatic. The aromatic hydrocarbon group and the alicyclic hydrocarbon group may have an aliphatic hydrocarbon group (e.g., an alkyl group, an alkenyl group, an alkynyl group) as a substituent. The number of carbon atoms in the aliphatic hydrocarbon group as a substituent may be, for example, 1 to 30, 1 to 20, 1 to 10, 1 to 6, or 1 to 4.
[0062] Examples of the aromatic hydrocarbon group include aromatic hydrocarbon groups having 24 or less carbon atoms (e.g., 6 to 24). The number of carbon atoms in the aromatic hydrocarbon group may be 20 or less (e.g., 6 to 20), 14 or less (e.g., 6 to 14), or 12 or less (e.g., 6 to 12). Examples of the aromatic hydrocarbon group include aryl groups and bisaryl groups. Examples of the aryl group include phenyl groups and naphthyl groups. Examples of the bisaryl group include monovalent groups corresponding to bisarenes. Examples of bisarenes include biphenyl, bisarylalkanes (e.g., bisC 6-10 Aryl C 1-4 Alkanes (such as 2,2-bisphenylpropane, etc.) are examples.
[0063] Examples of the alicyclic hydrocarbon group include alicyclic hydrocarbon groups having 16 or less carbon atoms. The alicyclic hydrocarbon group may be a cross-linked cyclic hydrocarbon group. The number of carbon atoms in the alicyclic hydrocarbon group may be 10 or less or 8 or less. The number of carbon atoms in the alicyclic hydrocarbon group may be, for example, 5 or more, or 6 or more.
[0064] The alicyclic hydrocarbon group may have 5 (or 6) or more and 16 (or less), 5 (or 6) or more and 10 (or less), or 5 (or 6) or more and 8 (or less) carbon atoms.
[0065] Examples of alicyclic hydrocarbon groups include cycloalkyl groups (cyclopentyl, cyclohexyl, cyclooctyl, etc.), cycloalkenyl groups (cyclohexenyl, cyclooctenyl, etc.), etc. Alicyclic hydrocarbon groups also include hydrogenated products of the above aromatic hydrocarbon groups.
[0066] From the viewpoint of facilitating thin adhesion of the polymer compound (P) to the lead surface, among the hydrocarbon groups, an aliphatic hydrocarbon group is preferred. The aliphatic hydrocarbon group may be saturated or unsaturated. Examples of the aliphatic hydrocarbon group include an alkyl group, an alkenyl group, an alkynyl group, a dienyl group having two carbon-carbon double bonds, and a trienyl group having three carbon-carbon double bonds. The aliphatic hydrocarbon group may be either linear or branched.
[0067] The number of carbon atoms in the aliphatic hydrocarbon group is, for example, 30 or less, and may be 26 or less or 22 or less, 20 or less or 16 or less, 14 or less or 10 or less, or 8 or less or 6 or less. The lower limit of the number of carbon atoms depends on the type of the aliphatic hydrocarbon group, and is 1 or more for an alkyl group, 2 or more for an alkenyl group and an alkynyl group, 3 or more for a dienyl group, and 4 or more for a trienyl group. Among these, alkyl groups and alkenyl groups are preferred from the viewpoint of facilitating thin adhesion of the polymer compound (P) to the lead surface.
[0068] Specific examples of alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, i-pentyl, s-pentyl, 3-pentyl, t-pentyl, n-hexyl, 2-ethylhexyl, n-octyl, n-nonyl, n-decyl, i-decyl, undecyl, lauryl (dodecyl), tridecyl, myristyl, pentadecyl, cetyl, heptadecyl, stearyl, icosyl, henicosyl, and behenyl.
[0069] Specific examples of the alkenyl group include vinyl, 1-propenyl, allyl, cis-9-heptadecen-1-yl, palmitoleyl, and oleyl. The alkenyl group is, for example, 2-30 Alkenyl group or C 2-26 may be an alkenyl group, C 2-22 Alkenyl group or C 2-20 may be an alkenyl group, C 10-20 It may be an alkenyl group.
[0070] Among the polymer compounds (P), oxy C 2-4 Ethers of hydroxy compounds with repeating alkylene units and oxy C 2-4 It is preferable to use at least one selected from the group consisting of esters of hydroxy compounds having a repeating structure of alkylene units, since this can further enhance the effect of suppressing the decrease in charge acceptance. In addition, the amount of electricity in overcharge can be reduced even when these polymer compounds (P) are used. Among these polymer compounds (P), those having a repeating structure of oxypropylene units or those having a repeating structure of oxyethylene units are preferable.
[0071] The polymer compound (P) may have one or more hydrophobic groups. Examples of the hydrophobic group include, among the above-mentioned hydrocarbon groups, aromatic hydrocarbon groups, alicyclic hydrocarbon groups, and long-chain aliphatic hydrocarbon groups. Examples of the long-chain aliphatic hydrocarbon group include, among the above-mentioned aliphatic hydrocarbon groups (alkyl groups, alkenyl groups, etc.), groups having 8 or more carbon atoms, preferably 12 or more, and more preferably 16 or more. Among them, the polymer compound (P) having a long-chain aliphatic hydrocarbon group is preferable because it is less likely to cause excessive adsorption to lead and further enhances the effect of suppressing the decrease in charge acceptance. The polymer compound (P) may have at least one hydrophobic group that is a long-chain aliphatic hydrocarbon group. The number of carbon atoms of the long-chain aliphatic hydrocarbon group may be 30 or less, 26 or less, or 22 or less.
[0072] The carbon number of the long-chain aliphatic hydrocarbon group may be 8 or more (or 12 or more) and 30 or less, 8 or more (or 12 or more) and 26 or less, 8 or more (or 12 or more) and 22 or less, 10 or more and 30 or less (or 26 or less), or 10 or more and 22 or less.
[0073] Among the polymer compounds (P), those having a hydrophilic group and a hydrophobic group correspond to nonionic surfactants. The repeating structure of the oxyethylene unit exhibits high hydrophilicity and can become the hydrophilic group in the nonionic surfactant. Therefore, it is preferable that the polymer compound (P) having the hydrophobic group contains a repeating structure of the oxyethylene unit. Such a polymer compound (P) can selectively adsorb to lead while suppressing excessive coverage of the lead surface due to the balance between hydrophobicity and high hydrophilicity due to the repeating structure of the oxyethylene unit, so that the effect of suppressing the decrease in charge acceptance can be further enhanced while reducing the amount of overcharge electricity. Such a polymer compound (P) can ensure high adsorption to lead even if it has a relatively low molecular weight (for example, Mn is 1000 or less).
[0074] Among the above polymer compounds (P), polyoxypropylene-polyoxyethylene block copolymers, etherified products of hydroxy compounds having a repeating structure of oxyethylene units, and esterified products of hydroxy compounds having a repeating structure of oxyethylene units correspond to nonionic surfactants.
[0075] Examples of the polymer compound (P) having a hydrophobic group and containing a repeating structure of an oxyethylene unit include etherified polyethylene glycol (such as alkyl ether), esterified polyethylene glycol (such as carboxylate), etherified polyethylene oxide adduct of the above polyol (such as alkyl ether), and esterified polyethylene oxide adduct of the above polyol (such as triol or higher polyol), etc. Specific examples of such polymer compounds (P) include polyethylene glycol oleate, polyethylene glycol dioleate, polyethylene glycol dilaurate, polyethylene glycol distearate, polyoxyethylene coconut oil fatty acid sorbitan, polyoxyethylene sorbitan oleate, polyoxyethylene sorbitan stearate, polyoxyethylene lauryl ether, polyoxyethylene tetradecyl ether, polyoxyethylene cetyl ether, etc., but are not limited thereto. Among them, the use of esterified polyethylene glycol, esterified polyethylene oxide adduct of the above polyol, etc. is preferable because it can ensure higher charge acceptance and significantly reduce the amount of overcharge electricity.
[0076] Oxy C is more effective in reducing the amount of overcharged electricity and is easier to secure higher charge acceptance. 2-4 It is also preferable that the repeating structure of alkylene contains at least a repeating structure of an oxypropylene unit. In this case, the charge acceptance tends to be lower than that of a repeating structure of an oxyethylene unit, but even in this case, it is possible to ensure high charge acceptance while suppressing the amount of overcharge electricity to a low level. The polymer compound (P) containing an oxypropylene unit is 1 In the chemical shift of the H-NMR spectrum, peaks derived from -CH< and -CH2- of the oxypropylene unit are present in the range of 3.2 ppm to 3.8 ppm. The peaks are split due to differences in electron density around the nuclei of the hydrogen atoms in these groups. Such a polymer compound (P) has 1In the chemical shift of the H-NMR spectrum, for example, there are peaks in the range of 3.2 ppm to 3.42 ppm and in the range of more than 3.42 ppm to 3.8 ppm. The peak in the range of 3.2 ppm to 3.42 ppm is derived from -CH2-, and the peak in the range of more than 3.42 ppm to 3.8 ppm is derived from -CH< and -CH2-.
[0077] Examples of the polymer compound (P) containing at least a repeating structure of an oxypropylene unit include polypropylene glycol, a copolymer containing a repeating structure of an oxypropylene unit, a polypropylene oxide adduct of the above polyol, or an ether or ester thereof. Examples of the copolymer include an oxypropylene-oxyalkylene copolymer (wherein the oxyalkylene is a C alkylene other than oxypropylene). 2-4 Examples of the oxypropylene-oxyalkylene copolymer include oxypropylene-oxyethylene copolymer and oxypropylene-oxytrimethylene copolymer. The oxypropylene-oxyalkylene copolymer may be called polyoxypropylene-polyoxyalkylene copolymer (for example, polyoxypropylene-polyoxyethylene copolymer). The oxypropylene-oxyalkylene copolymer may be a block copolymer (for example, polyoxypropylene-polyoxyethylene block copolymer). Examples of the etherified product include polypropylene glycol alkyl ether and alkyl ether of oxypropylene-oxyalkylene copolymer (alkyl ether of polyoxypropylene-polyoxyethylene copolymer, etc.). Examples of the esterified product include polypropylene glycol ester of carboxylic acid and carboxylic acid ester of oxypropylene-oxyalkylene copolymer (carboxylic acid ester of polyoxypropylene-polyoxyethylene copolymer, etc.).
[0078] Examples of the polymer compound (P) containing at least a repeating structure of an oxypropylene unit include polypropylene glycol, polyoxypropylene-polyoxyethylene copolymers (such as polyoxypropylene-polyoxyethylene block copolymers), polyoxyethylene-polyoxypropylene alkyl ethers (such as the above-mentioned R 2 alkyl ether (butyl ether, etc.) in which R is an alkyl having 10 or less carbon atoms (or 8 or less or 6 or less), polypropylene glycol carboxylate (the above R 3 Examples of the polymer compound (P) include, but are not limited to, polypropylene glycol carboxylates (such as polypropylene glycol acetates) in which the alkyl group has 10 or less carbon atoms (or 8 or less, or 6 or less), and polypropylene oxide adducts of triol or higher polyols (such as polypropylene oxide adducts of glycerin).
[0079] In the polymer compound (P) containing a repeating structure of oxypropylene units, the ratio of the oxypropylene units is, for example, 5 mol% or more, and may be 10 mol% or more or 20 mol% or more. The ratio of the oxypropylene units is, for example, 100 mol% or less. In the above copolymer, the ratio of the oxypropylene units may be 90 mol% or less, 75 mol% or less, or 60 mol% or less.
[0080] In the polymer compound (P) containing a repeating structure of oxypropylene units, the proportion of the oxypropylene units may be 5 mol% or more and 100 mol% or less (or 90 mol% or less), 10 mol% or more and 100 mol% or less (or 90 mol% or less), 20 mol% or more and 100 mol% or less (or 90 mol% or less), 5 mol% or more and 75 mol% or less (or 60 mol% or less), 10 mol% or more and 75 mol% or less (or 60 mol% or less), or 20 mol% or more and 75 mol% or less (or 60 mol% or less).
[0081] The polymer compound (P) is preferably oxy-C, in order to increase the adsorption of the polymer compound (P) to lead and to facilitate the formation of a linear structure. 2-4 It is preferable that the polymer compound (P) contains a large number of alkylene units. Such a polymer compound (P) contains, for example, an oxygen atom bonded to the terminal group and a -CH2- group and / or a -CH< group bonded to the oxygen atom. 1 In the H-NMR spectrum, the integral value V1 of the peaks between 3.2 ppm and 3.8 ppm is the sum of the integral values of the given peaks V SUM Here, the total integral value of the peak, V SUM is the sum of the integral value V1, the integral value of the peak of the hydrogen atom of the -CH2- group, and the integral value of the peak of the hydrogen atom of the -CH< group. This ratio is, for example, 50% or more, and may be 80% or more. From the viewpoint of further enhancing the effect of reducing the overcharge electricity amount and easily ensuring higher charge acceptance, the above ratio is preferably 85% or more, and more preferably 90% or more. For example, when the polymer compound (P) has an -OH group at its terminal and also has a -CH2- group or a -CH< group bonded to the oxygen atom of the -OH group, 1 In the H-NMR spectrum, the peaks of the hydrogen atoms of the -CH2- group and -CH< group have chemical shifts in the range of more than 3.8 ppm to 4.0 ppm.
[0082] The negative electrode material may contain one type of polymer compound (P) or two or more types of polymer compounds (P).
[0083] The polymer compound (P) may include, for example, a compound with Mn of 5 million or less, a compound with Mn of 3 million or less or 2 million or less, a compound with Mn of 500,000 or less or 100,000 or less, or a compound with Mn of 50,000 or less or 20,000 or less. From the viewpoint of ensuring higher charge acceptance, the polymer compound (P) preferably includes a compound with Mn of 10,000 or less, a compound with Mn of 5,000 or less or 4,000 or less, or a compound with Mn of 3,000 or less or 2,500 or less. The Mn of such a compound may be 300 or more or 400 or more, or may be 500 or more. From the viewpoint of further enhancing the effect of reducing the overcharged amount of electricity, the Mn of such a compound is preferably 1,000 or more, more preferably 1,500 or more or 1,800 or more. As the polymer compound (P), two or more compounds with different Mn may be used. That is, the polymer compound (P) may have multiple Mn peaks in the molecular weight distribution.
[0084] The Mn of the above compounds is 300 or more (or 400 or more) and 5 million or less, 300 or more (or 400 or more) and 3 million or less, 300 or more (or 400 or more) and 2 million or less, 300 or more (or 400 or more) and 500,000 or less, 300 or more (or 400 or more) and 100,000 or less, 300 or more (or 400 or more) and 50,000 or less, 300 or more (or 400 or more) and 20,000 or less, 300 or more (or 400 or more) and 10,000 or less, 300 or more (or 400 or more) and 5,000 or less, 300 or more (or 400 or more) 4000 or less, 300 or more (or 400 or more) 3000 or less, 300 or more (or 400 or more) 2500 or less, 500 or more (or 1000 or more) 5 million or less, 500 or more (or 1000 or more) 3 million or less, 500 or more (or 1000 or more) 2 million or less, 500 or more (or 1000 or more) 500,000 or less, 500 or more (or 1000 or more) 100,000 or less, 500 or more (or 1000 or more) 50,000 or less, 500 or more (or 1000 or more) 20,000 or less, 500 or more (or 1,000 or more) 10,000 or less, 500 or more (or 1,000 or more) 5,000 or less, 500 or more (or 1,000 or more) 4,000 or less, 500 or more (or 1,000 or more) 3,000 or less, 500 or more (or 1,000 or more) 2,500 or less, 1,500 or more (or 1,800 or more) 5 million or less, 1,500 or more (or 1,800 or more) 3 million or less, 1,500 or more (or 1,800 or more) 2 million or less, 1,500 or more (or 1,800 or more) but not exceeding 500,000, 1,500 or more (or 1,800 or more) but not exceeding 100,000, 1,500 or more (or 1,800 or more) but not exceeding 50,000, 1,500 or more (or 1,800 or more) but not exceeding 20,000, 1,500 or more (or 1,800 or more) but not exceeding 10,000, 1,500 or more (or 1,800 or more) but not exceeding 5,000, 1,500 or more (or 1,800 or more) but not exceeding 4,000, 1,500 or more (or 1,800 or more) but not exceeding 3,000, or 1,500 or more (or 1,800 or more) but not exceeding 2,500.
[0085] The content of the polymer compound (P) in the negative electrode material is, for example, 8 ppm or more, and may be 10 ppm or more, based on mass. From the viewpoint of further enhancing the effect of reducing the overcharge electricity amount, the content of the polymer compound (P) in the negative electrode material is, for example, 20 ppm or more, and more preferably 30 ppm or more, based on mass. The content of the polymer compound (P) in the negative electrode material is, for example, 1000 ppm or less, and may be less than 1000 ppm, 700 ppm or less, 600 ppm or less, or 500 ppm or less, based on mass. From the viewpoint of easily ensuring higher charge acceptance, the content of the polymer compound (P) in the negative electrode material is, for example, 400 ppm or less, more preferably 300 ppm or less, and may be 200 ppm or less or 160 ppm or less, 150 ppm or less or 120 ppm or less, or may be 100 ppm or less, based on mass.
[0086] The content (by mass) of polymer compounds (P) in the negative electrode material is 8 ppm or more (or 10 ppm or more) and 1000 ppm or less, 8 ppm or more (or 10 ppm or more) and less than 1000 ppm, 8 ppm or more (or 10 ppm or more) and 700 ppm or less, 8 ppm or more (or 10 ppm or more) and 600 ppm or less, 8 ppm or more (or 10 ppm or more) and 500 ppm or less, 8 ppm or more (or is 10ppm or more) 400ppm or less, 8ppm or more (or 10ppm or more) 300ppm or less, 8ppm or more (or 10ppm or more) 200ppm or less, 8ppm or more (or 10ppm or more) 160ppm or less, 8ppm or more (or 10ppm or more) 150ppm or less, 8ppm or more (or 10ppm or more) 120ppm or less, 8ppm or more (or 10ppm or more) 100ppm m or less, 20 ppm or more (or 30 ppm or more) 1000 ppm or less, 20 ppm or more (or 30 ppm or more) less than 1000 ppm, 20 ppm or more (or 30 ppm or more) 700 ppm or less, 20 ppm or more (or 30 ppm or more) 600 ppm or less, 20 ppm or more (or 30 ppm or more) 500 ppm or less, 20 ppm or more (or 30 ppm or more) 400 ppm or less, 20 It may be 20 ppm or more (or 30 ppm or more) but not more than 300 ppm, 20 ppm or more (or 30 ppm or more) but not more than 200 ppm, 20 ppm or more (or 30 ppm or more) but not more than 160 ppm, 20 ppm or more (or 30 ppm or more) but not more than 150 ppm, 20 ppm or more (or 30 ppm or more) but not more than 120 ppm, or 20 ppm or more (or 30 ppm or more) but not more than 100 ppm.
[0087] (Organic shrink-proofing agent) Organic shrink-preventing agents are generally classified into lignin compounds and synthetic organic shrink-preventing agents. Synthetic organic shrink-preventing agents can also be said to be organic shrink-preventing agents other than lignin compounds. Examples of organic shrink-preventing agents contained in the negative electrode material include lignin compounds and synthetic organic shrink-preventing agents. The negative electrode material may contain one type of organic shrink-preventing agent, or two or more types of organic shrink-preventing agents. Examples of the organic shrink-preventing agent (B) include some of the synthetic organic shrink-preventing agents described below.
[0088] Examples of the lignin compound include lignin and lignin derivatives. Examples of the lignin derivatives include lignin sulfonic acid or salts thereof (alkali metal salts (sodium salts, etc.)).
[0089] The synthetic organic shrink-proofing agent is an organic polymer containing elemental sulfur, and generally contains multiple aromatic rings in the molecule and elemental sulfur as a sulfur-containing group. Among the sulfur-containing groups, sulfonic acid groups or sulfonyl groups, which are stable, are preferred. The sulfonic acid groups may exist in the acid form or in the salt form such as Na salt. is suppressed, and high charge acceptance can be ensured.
[0090] As the organic shrink-proofing agent, it is also preferable to use a condensation product containing at least an aromatic compound unit. For example, such a condensation product may be a condensation product of an aromatic compound with an aldehyde compound (at least one selected from the group consisting of aldehydes (e.g., formaldehyde) and their condensates). The organic shrink-proofing agent may contain one type of aromatic compound unit, or may contain two or more types of aromatic compound units. The aromatic compound unit refers to a unit derived from an aromatic compound incorporated in the condensation product. The condensation product using a bisphenol compound as the aromatic compound is included in the organic shrink-proofing agent (B).
[0091] Examples of the aromatic rings that aromatic compounds have include benzene rings and naphthalene rings. When aromatic compounds have multiple aromatic rings, the multiple aromatic rings may be linked by direct bonds or linking groups (e.g., alkylene groups (including alkylidene groups), sulfone groups) or the like. Examples of such structures include bisarene structures (biphenyl, bisphenylalkane, bisphenylsulfone, etc.). Examples of aromatic compounds include compounds having the above aromatic rings and at least one selected from the group consisting of hydroxyl groups and amino groups. The hydroxyl group or amino group may be directly bonded to the aromatic ring, or may be bonded as an alkyl chain having a hydroxyl group or amino group. The hydroxyl group also includes salts of the hydroxyl group (-OMe). The amino group also includes salts of the amino group (specifically, salts with anions). Examples of Me include alkali metals (Li, K, Na, etc.) and metals of Group 2 of the periodic table (Ca, Mg, etc.).
[0092] As the aromatic compound, bisarene compounds [bisphenol compounds, hydroxybiphenyl compounds, bisarene compounds having an amino group (bisarylalkane compounds having an amino group, bisarylsulfone compounds having an amino group, biphenyl compounds having an amino group, etc.), hydroxyarene compounds (hydroxynaphthalene compounds, phenol compounds, etc.), aminoarene compounds (aminonaphthalene compounds, aniline compounds (aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc.)), etc.] are preferred. The aromatic compound may further have a substituent. The organic shrinkage inhibitor may contain one or more of the residues of these compounds. As the bisphenol compound, bisphenol A, bisphenol S, bisphenol F, etc. are preferred.
[0093] The condensate preferably contains at least a unit of an aromatic compound having a sulfur-containing group. In particular, the use of a condensate containing at least a unit of a bisphenol compound having a sulfur-containing group is advantageous in terms of ensuring higher charge acceptance. From the viewpoint of increasing the effect of reducing the amount of overcharge electricity, it is also preferable to use a condensate of an aldehyde compound with a naphthalene compound having a sulfur-containing group and at least one selected from the group consisting of a hydroxyl group and an amino group.
[0094] The sulfur-containing group may be directly bonded to an aromatic ring contained in the compound, or may be bonded to the aromatic ring as an alkyl chain having a sulfur-containing group. The sulfur-containing group is not particularly limited, and examples thereof include a sulfonyl group, a sulfonic acid group, or a salt thereof.
[0095] Also, as the organic shrink-proofing agent, for example, at least one condensate containing at least one selected from the group consisting of the above-mentioned bisarene compound units and monocyclic aromatic compound units (hydroxyarene compounds and / or aminoarene compounds, etc.) may be used. The organic shrink-proofing agent may at least contain a condensate containing a bisarene compound unit and a monocyclic aromatic compound unit (particularly, a hydroxyarene compound). Such a condensate may be a condensate of a bisarene compound and a monocyclic aromatic compound with an aldehyde compound. As the hydroxyarene compound, a phenolsulfonic acid compound (such as phenolsulfonic acid or a substituted product thereof) is preferable. As the aminoarene compound, aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc. are preferable. As the monocyclic aromatic compound, a hydroxyarene compound is preferable.
[0096] The negative electrode material may contain, for example, an organic shrink-proofing agent (first organic shrink-proofing agent) having a sulfur element content of 2000 μmol / g or more among the above organic shrink-proofing agents. Examples of the first organic shrink-proofing agent include the above synthetic organic shrink-proofing agents (such as the above condensates).
[0097] The sulfur element content of the first organic shrinkage inhibitor may be 2000 μmol / g or more, and preferably 3000 μmol / g or more. The upper limit of the sulfur element content of the organic shrinkage inhibitor is not particularly limited, and from the viewpoint of further enhancing the effect of reducing the amount of overcharge electricity, it is preferably 9000 μmol / g or less, and more preferably 8000 μmol / g or less.
[0098] The sulfur element content of the first organic shrink inhibitor may be, for example, 2000 μmol / g or more (or 3000 μmol / g or more) and 9000 μmol / g or less, or 2000 μmol / g or more (or 3000 μmol / g or more) and 8000 μmol / g or less.
[0099] The first organic shrink-preventing agent includes a condensate containing a unit of an aromatic compound having a sulfur-containing group, and the condensate may include at least a unit of a bisphenol compound as the unit of the aromatic compound. That is, the first organic shrink-preventing agent may be an organic shrink-preventing agent (B). In that case, in this specification, the first organic shrink-preventing agent can be read as an organic shrink-preventing agent (B).
[0100] The weight average molecular weight (Mw) of the first organic shrink-proofing agent is preferably equal to or greater than 7000. The Mw of the first organic shrink-proofing agent is, for example, equal to or less than 100,000, and may be equal to or less than 20,000.
[0101] The negative electrode material may contain, for example, an organic shrink-proofing agent (second organic shrink-proofing agent) having a sulfur element content of less than 2000 μmol / g. The second organic shrink-proofing agent may be, among the above organic shrink-proofing agents, a lignin compound, a synthetic organic shrink-proofing agent (e.g., a bisphenol condensate), or the like. The sulfur element content of the second organic shrink-proofing agent is preferably 1000 μmol / g or less, and may be 800 μmol / g or less. The lower limit of the sulfur element content in the second organic shrink-proofing agent is not particularly limited, but is, for example, 400 μmol / g or more.
[0102] The Mw of the second organic shrink-proofing agent is, for example, less than 7000. The Mw of the second organic shrink-proofing agent is, for example, 3000 or more.
[0103] The negative electrode material may contain a second organic shrink-proofing agent in addition to the first organic shrink-proofing agent. When the first organic shrink-proofing agent and the second organic shrink-proofing agent are used in combination, the mass ratio thereof can be selected arbitrarily.
[0104] The content of the organic shrinkage inhibitor contained in the negative electrode material is, for example, 0.005% by mass or more, and may be 0.01% by mass or more. When the content of the organic shrinkage inhibitor is in such a range, a high low-temperature high-rate discharge capacity can be ensured. The content of the organic shrinkage inhibitor is, for example, 1.0% by mass or less, and may be 0.5% by mass or less. From the viewpoint of further enhancing the effect of suppressing the decrease in charge acceptance, the content of the organic shrinkage inhibitor is preferably 0.3% by mass or less, more preferably 0.25% by mass or less, further preferably 0.2% by mass or less or 0.15% by mass or less, and may be 0.12% by mass or less.
[0105] The content of the organic shrinkage preventer in the negative electrode material may be 0.005% by mass or more (or 0.01% by mass or more) to 1.0% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) to 0.5% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) to 0.3% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) to 0.25% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) to 0.2% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) to 0.15% by mass or less, or 0.005% by mass or more (or 0.01% by mass or more) to 0.12% by mass or less.
[0106] (carbonaceous material) Carbon black, graphite, hard carbon, soft carbon, etc. can be used as the carbonaceous material contained in the negative electrode material. Examples of carbon black include acetylene black, furnace black, lamp black, etc. Furnace black also includes Ketjen Black (trade name). Graphite may be any carbonaceous material containing a graphite-type crystal structure, and may be either artificial graphite or natural graphite. The negative electrode material may contain one type of carbonaceous material, or may contain two or more types.
[0107] The content of the carbonaceous material in the negative electrode material is, for example, 0.05 mass% or more, and may be 0.10 mass% or more.The content of the carbonaceous material is, for example, 5 mass% or less, and may be 3 mass% or less.
[0108] The content of the carbonaceous material in the negative electrode material may be 0.05% by mass to 5% by mass, 0.05% by mass to 3% by mass, 0.10% by mass to 5% by mass, or 0.10% by mass to 3% by mass.
[0109] (Analysis of negative electrode materials or components) The following describes a method for analyzing the negative electrode material or its constituents. Prior to measurement or analysis, a fully charged lead-acid battery is disassembled to obtain a negative plate to be analyzed. The obtained negative plate is washed with water to remove sulfuric acid from the negative plate. The washing is performed by pressing a pH test paper against the washed surface of the negative plate until it is confirmed that the color of the test paper does not change. However, the washing time is within 2 hours. The washed negative plate is dried at 60±5°C for about 6 hours in a reduced pressure environment. If the negative plate contains an attachment material, the attachment material is removed as necessary. Next, a sample (hereinafter referred to as sample A) is obtained by separating the negative electrode material from the negative plate. Sample A is crushed as necessary and subjected to analysis. The mass of the negative electrode material in the negative plate is obtained by measuring the mass of sample A.
[0110] (1) Measurement of surface area and content of barium sulfate The surface area of barium sulfate in the negative electrode material is measured using crushed sample A. The measurement is performed according to the following procedure. First, 500 mL of nitric acid (concentration: 20 mass%) is added to 100 g of crushed sample A, and the mixture is heated for about 20 minutes to dissolve the lead component. The liquid thus obtained is filtered to filter out solids such as carbonaceous material and barium sulfate. The obtained solids are dispersed in water to obtain a dispersion, and then a sieve is used to remove components other than the carbonaceous material and barium sulfate (e.g., reinforcing material) from the dispersion. Next, the dispersion is subjected to suction filtration using a membrane filter. The membrane filter is dried together with the sample filtered out by this filtration in a dryer at 110°C ± 5°C. The filtered sample is a mixed sample of carbonaceous material and barium sulfate. The mixed sample after drying (hereinafter, sometimes referred to as "sample C") is recovered from the membrane filter.
[0111] Next, the mass (M(C+Ba)) of the collected sample C is measured. Then, the surface area (S(C+Ba)) of the sample C is measured by the nitrogen adsorption (BET) method. Next, the sample C whose surface area has been measured is dispersed in 100 mL of an aqueous solution to obtain a dispersion. The aqueous solution has a NaOH concentration of 1 mol / L and an EDTA concentration of 0.3 mol / L. The obtained dispersion is stirred at 40°C for 20 hours to dissolve the barium sulfate. The liquid thus obtained is filtered, and the filtered solid is dried to obtain only the carbonaceous material. The mass (M(C)) of the obtained carbonaceous material is measured. In addition, the surface area (S(C)) of the obtained carbonaceous material is measured by the nitrogen adsorption (BET) method. The surface area (S(Ba)) of the barium sulfate is obtained by subtracting the surface area S(C) from the surface area (S(C+Ba)). The surface area (Z) of barium sulfate per 1 g of negative electrode material is calculated by dividing the surface area (S(Ba)) by the mass of sample A (100 g in this case). The mass of barium sulfate (M(Ba)) is calculated by subtracting the mass (M(C)) from the mass (M(C+Ba)). The content (mass%) of barium sulfate in the negative electrode material can be calculated from the mass (M(Ba)) and the mass (100 g in this case) of sample A (negative electrode material).
[0112] (2) Measurement of the average particle size of barium sulfate To measure the average particle size of barium sulfate in the negative electrode material, sample A is used without grinding. First, 50 mL of nitric acid (concentration: 20 mass%) is added to 10 g of sample A, and the lead component is dissolved by heating for about 20 minutes. The liquid thus obtained is filtered to filter out solids such as carbonaceous material and barium sulfate. The obtained solids are dispersed in water to obtain a dispersion, and then components other than the carbonaceous material and barium sulfate (e.g., reinforcing material) are removed from the dispersion using a sieve. Next, the dispersion is subjected to suction filtration using a membrane filter whose mass has been measured in advance, and the solids are filtered out. The membrane filter together with the filtered sample (solids) is dried in a dryer at 110°C ± 5°C. The filtered sample is a mixed sample of carbonaceous material and barium sulfate. This mixed sample is observed with a scanning electron microscope (SEM) and EDS analysis is performed. Through this observation and analysis, barium sulfate (barium sulfate particles) is identified and its particle size is measured. Here, the particle size is the circle equivalent diameter. The particle size measurement is performed on 1,000 randomly selected barium sulfate particles, and the average value of the measured particle sizes is taken as the average particle size of barium sulfate. In other words, the average particle size of barium sulfate means the average particle size measured by the method described herein.
[0113] (3) Analysis of polymer compounds (P) (3-1) Qualitative analysis of polymer compounds (P) A crushed sample A is used. 150.0±0.1 mL of chloroform is added to 100.0±0.1 g of sample A, and the mixture is stirred at 20±5°C for 16 hours to extract the polymer compound (P). The solid content is then removed by filtration. The polymer compound (P) obtained by extraction is dissolved in a chloroform solution or by drying the chloroform solution, and information is obtained from at least one of infrared spectroscopy, ultraviolet-visible absorption spectroscopy, NMR spectroscopy, LC-MS, and pyrolysis GC-MS to identify the polymer compound (P).
[0114] From the chloroform solution in which the polymer compound (P) obtained by extraction is dissolved, chloroform is distilled off under reduced pressure to recover the chloroform-soluble matter. The chloroform-soluble matter is dissolved in deuterated chloroform and then stirred under the following conditions: 1 1H-NMR spectrum is measured. 1 From the H-NMR spectrum, a peak with a chemical shift in the range of 3.2 ppm to 3.8 ppm is confirmed. Also, from the peak in this range, oxy C 2-4 Identify the type of alkylene unit.
[0115] Apparatus: AL400 nuclear magnetic resonance spectrometer manufactured by JEOL Ltd. Observation frequency: 395.88MHz Pulse width: 6.30μs Pulse repetition time: 74.1411 seconds Accumulation count: 32 Measurement temperature: room temperature (20~35℃) Standard: 7.24 ppm Sample tube diameter: 5mm
[0116] 1 From the H-NMR spectrum, the integral value (V1) of the peaks present in the chemical shift range of 3.2 ppm to 3.8 ppm is determined. In addition, for each of the hydrogen atoms of the -CH2- group and -CH< group bonded to the oxygen atom bonded to the terminal group of the polymer compound (P), 1 The sum (V2) of the integral values of the peaks in the H-NMR spectrum is calculated. Then, from V1 and V2, the percentage of V1 in the sum of V1 and V2 (=V1 / (V1+V2)×100(%)) is calculated.
[0117] In addition, in the qualitative analysis, 1 When calculating the integral value of a peak in a H-NMR spectrum, 1In the H-NMR spectrum, two points without significant signals are determined so as to sandwich the corresponding peak, and each integral value is calculated using a straight line connecting these two points as a baseline. For example, for a peak that exists in a chemical shift range of 3.2 ppm to 3.8 ppm, a straight line connecting two points on the spectrum between 3.2 ppm and 3.8 ppm is used as the baseline. For example, for a peak that exists in a chemical shift range of more than 3.8 ppm to 4.0 ppm, a straight line connecting two points on the spectrum between 3.8 ppm and 4.0 ppm is used as the baseline.
[0118] (3-2) Quantitative analysis of polymer compounds (P) The appropriate amount of the chloroform soluble matter was measured with an accuracy of ±0.0001 g. r (g) Dissolve in deuterated chloroform together with tetrachloroethane (TCE), 1 Measure the H-NMR spectrum. The integral value (S a ) and the integral value of the peak due to TCE (S r ) and calculate the mass content C of the polymer compound (P) in the negative electrode material from the following formula: n Calculate the ppm.
[0119] C n =S a / S r ×N r / N a ×M a / M r ×m r / m×1000000 (In the formula, M a The molecular weight of the structure that shows a peak in the chemical shift range of 3.2 to 3.8 ppm (more specifically, oxy C 2-4 (the molecular weight of the repeating structure of alkylene units) and N a is the number of hydrogen atoms attached to the carbon atoms in the main chain of the repeating unit. r、 M r are the number of hydrogen atoms contained in the molecule of the reference material, the molecular weight of the reference material, and m (g) is the mass of the negative electrode material used for extraction.) In addition, the standard substance in this analysis is TCE, so N r =2, M r = 168. Also, m = 100.
[0120] For example, when the polymer compound (P) is polypropylene glycol, M a is 58, and N a is 3. When the polymer compound (P) is polyethylene glycol, M a is 44, and N a is 4. N a and M. a is the N of each monomer unit a Value and M a The value is calculated by averaging the molar ratio (mol %) of each monomer unit contained in the repeating structure.
[0121] In addition, in the quantitative analysis, 1 The integral value of the peak in the H-NMR spectrum is determined using data processing software “ALICE” manufactured by JEOL Ltd.
[0122] (3-3) Mn measurement of polymer compound (P) Using the above chloroform solubles, GPC measurement of polymer compound (P) is performed using the following apparatus under the following conditions. Separately, a calibration curve (calibration curve) is created from a plot of Mn of the standard substance versus elution time. Based on this calibration curve and the GPC measurement results of polymer compound (P), Mn of polymer compound (P) is calculated. However, esterified or etherified products may be in a decomposed state in the chloroform solubles.
[0123] Analysis system: 20A system (Shimadzu Corporation) Column: Two GPC KF-805L (Shodex) columns connected in series Column temperature: 30℃±1℃ Mobile phase: Tetrahydrofuran Flow rate: 1mL / min. Concentration: 0.20% by mass Injection volume: 10μL Standard substance: polyethylene glycol (Mn=2,000,000, 200,000, 20,000, 2,000, 200) Detector: Differential refractive index detector (Shodex RI-201H)
[0124] (4) Analysis of organic shrinkage inhibitors (4-1) Qualitative analysis of organic shrinkage inhibitors in negative electrode materials The crushed sample A is immersed in a 1 mol / L aqueous solution of sodium hydroxide to extract the organic shrink-preventing agent. Next, the first organic shrink-preventing agent and the second organic shrink-preventing agent are separated from the extract as necessary. For each of the separated products containing each organic shrink-preventing agent, insoluble components are removed by filtration, and the resulting solution is desalted, concentrated, and dried. Desalting is performed using a desalting column, or by passing the solution through an ion exchange membrane, or by placing the solution in a dialysis tube and immersing it in distilled water. This is dried to obtain a powder sample of the organic shrink-preventing agent (hereinafter referred to as sample B).
[0125] The type of organic shrink-proofing agent is identified by combining information obtained from the following: infrared spectrum measured using sample B of the organic shrink-proofing agent obtained in this manner; ultraviolet-visible absorption spectrum measured using an ultraviolet-visible spectrometer after diluting sample B with distilled water or the like; NMR spectrum of a solution obtained by dissolving sample B in a specified solvent such as heavy water; or information obtained from pyrolysis GC-MS, which can provide information on the individual compounds that make up the substance.
[0126] The first and second organic shrink-preventing agents are separated from the extract as follows. First, the extract is measured by infrared spectroscopy, NMR, and / or GC-MS to determine whether it contains multiple organic shrink-preventing agents. Next, the extract is analyzed by GPC to measure the molecular weight distribution. If the multiple organic shrink-preventing agents can be separated by molecular weight, the organic shrink-preventing agents are separated by column chromatography based on the difference in molecular weight. If separation based on the difference in molecular weight is difficult, one of the organic shrink-preventing agents is separated by precipitation separation using the difference in solubility that differs depending on the type and / or amount of functional groups that the organic shrink-preventing agents have. Specifically, the extract is dissolved in an aqueous NaOH solution, and an aqueous sulfuric acid solution is dropped into the mixture to adjust the pH of the mixture, thereby flocculating and separating one of the organic shrink-preventing agents. The separated material is dissolved again in an aqueous NaOH solution, and insoluble components are removed by filtration as described above. The remaining solution after separating one of the organic shrink-preventing agents is concentrated. The resulting concentrate contains the other organic shrinkage inhibitor, and the insoluble components are removed from the concentrate by filtration as described above.
[0127] (4-2) Quantitative determination of organic shrinkage inhibitor content in negative electrode material As in the above (4-1), a solution is obtained by removing insoluble components from each of the separated products containing the organic shrinkage inhibitor by filtration. The ultraviolet-visible absorption spectrum of each of the obtained solutions is measured. The content of each organic shrinkage inhibitor in the negative electrode material is determined using the intensity of the peak characteristic of each organic shrinkage inhibitor and a calibration curve prepared in advance.
[0128] In addition, when a lead-acid battery with an unknown content of organic shrink-proofing agent is obtained and the content of the organic shrink-proofing agent is measured, the structural formula of the organic shrink-proofing agent cannot be precisely specified, so that the same organic shrink-proofing agent cannot be used for the calibration curve. In this case, a calibration curve is created using the organic shrink-proofing agent extracted from the negative electrode of the battery and a separately available organic polymer that shows similar shapes in the ultraviolet-visible absorption spectrum, infrared spectroscopy spectrum, NMR spectrum, etc., and the content of the organic shrink-proofing agent is measured using the ultraviolet-visible absorption spectrum.
[0129] (4-3) Sulfur content in organic shrinkage inhibitors As in (4-1) above, after obtaining sample B of the organic shrink-proofing agent, the sulfur element in 0.1 g of the organic shrink-proofing agent is converted to sulfuric acid by the oxygen combustion flask method. At this time, sample B is burned in a flask containing an adsorption solution to obtain an eluate in which sulfate ions are dissolved in the adsorption solution. Next, the sulfur element content (c1) in 0.1 g of the organic shrink-proofing agent is obtained by titrating the eluate with barium perchlorate using thorin as an indicator. Next, c1 is multiplied by 10 to calculate the sulfur element content (μmol / g) in the organic shrink-proofing agent per 1 g.
[0130] (4-4) Mw measurement of organic shrinkage regulators As in (4-1) above, after obtaining sample B of the organic shrink-preventing agent, the GPC measurement of the organic shrink-preventing agent is carried out using the following apparatus under the following conditions. Separately, a calibration curve (calibration curve) is created from a plot of the Mw of the standard substance versus elution time. Based on this calibration curve and the GPC measurement results of the organic shrink-preventing agent, the Mw of the organic shrink-preventing agent is calculated.
[0131] GPC equipment: Build-up GPC system SD-8022 / DP-8020 / AS-8020 / CO-8020 / UV-8020 (Tosoh Corporation) Column: TSKgel G4000SWXL, G2000SWXL (7.8 mm I.D. x 30 cm) (Tosoh Corporation) Detector: UV detector, λ=210nm Eluent: A mixture of 1 mol / L NaCl aqueous solution: acetonitrile (volume ratio = 7:3) Flow rate: 1mL / min. Concentration: 10mg / mL Injection volume: 10μL Standard substance: Sodium polystyrene sulfonate (Mw=275,000, 35,000, 12,500, 7,500, 5,200, 1,680)
[0132] (others) The negative electrode plate can be formed by applying or filling a negative electrode paste onto a negative electrode current collector, aging and drying to prepare an unformed negative electrode plate, and then chemically forming the unformed negative electrode plate. The negative electrode paste is prepared, for example, by adding water and sulfuric acid (or an aqueous sulfuric acid solution) to lead powder, an organic shrinkage preventer (B), and, if necessary, at least one selected from the group consisting of a polymer compound (P), a carbonaceous material, and other additives, and kneading the mixture. When aging, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at a high humidity.
[0133] The formation can be carried out by immersing the plate group including the unformed negative plate in an electrolyte containing sulfuric acid in a lead-acid battery container and charging the plate group. However, the formation may be carried out before assembling the lead-acid battery or the plate group. The formation produces spongy lead.
[0134] (Positive plate) The positive electrode plate of the lead-acid battery can be classified into a paste type, a clad type, and the like. Either a paste type or a clad type positive electrode plate may be used. The paste type positive electrode plate includes a positive electrode current collector and a positive electrode material. The configuration of the clad type positive electrode plate is as described above.
[0135] The positive electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the positive electrode current collector because it is easy to support the positive electrode material.
[0136] As the lead alloy used for the positive electrode current collector, in terms of corrosion resistance and mechanical strength, Pb-Sb alloy, Pb-Ca alloy, Pb-Ca-Sn alloy are preferable. The positive electrode current collector may have a surface layer. The surface layer and the inner layer of the positive electrode current collector may have different compositions. The surface layer may be formed on a part of the positive electrode current collector. The surface layer may be formed only on the lattice part, only on the edge part, or only on the frame part of the positive electrode current collector.
[0137] The positive electrode material contained in the positive electrode plate contains a positive electrode active material (lead dioxide or lead sulfate) that develops capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives as necessary.
[0138] The unformed paste-type positive plate is obtained by filling a positive current collector with a positive electrode paste, aging and drying. The positive electrode paste is prepared by kneading lead powder, additives, water and sulfuric acid. The unformed clad-type positive plate is formed by filling a porous tube into which a core metal connected by a current collector is inserted with lead powder or lead powder in a slurry form, and connecting a plurality of tubes with a connecting member. Then, the unformed positive plate is formed to obtain a positive plate. The formation can be performed by charging the plate group in a state where the plate group including the unformed positive plate is immersed in an electrolyte containing sulfuric acid in a battery container of a lead-acid battery. However, the formation may be performed before assembling the lead-acid battery or the plate group.
[0139] The formation can be carried out by immersing an electrode plate group including unformed positive plates in an electrolyte solution containing sulfuric acid in a battery container of a lead-acid battery and charging the electrode plate group in this state. However, the formation may also be carried out before assembling the lead-acid battery or the electrode plate group.
[0140] (Separator) A separator may be disposed between the negative electrode plate and the positive electrode plate, and may be made of at least one material selected from a nonwoven fabric and a microporous membrane.
[0141] A nonwoven fabric is a mat in which fibers are intertwined without being woven, and is mainly composed of fibers. For example, 60% or more by mass of the nonwoven fabric is made of fibers. As the fibers, glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (polyethylene terephthalate fibers, etc.), pulp fibers, etc.) can be used. Among them, glass fibers are preferable. The nonwoven fabric may contain components other than fibers, such as acid-resistant inorganic powders and polymers as binders.
[0142] On the other hand, a microporous membrane is a porous sheet mainly composed of components other than fiber components, and can be obtained, for example, by extruding a composition containing a pore-forming agent into a sheet, and then removing the pore-forming agent to form pores. The microporous membrane is preferably made of an acid-resistant material, and is preferably made mainly of a polymer component. The polymer component is preferably polyolefin (polyethylene, polypropylene, etc.). The pore-forming agent can be at least one selected from the group consisting of polymer powder and oil.
[0143] The separator may be, for example, composed of only a nonwoven fabric or only a microporous membrane. Furthermore, the separator may be, as necessary, a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same materials, or a laminate of different or the same materials with recesses and projections interlocked.
[0144] The separator may be in a sheet shape or may be formed in a bag shape. A sheet-shaped separator may be sandwiched between the positive electrode plate and the negative electrode plate. Also, the electrode plate may be sandwiched between a folded sheet-shaped separator. In this case, the positive electrode plate sandwiched between the folded sheet-shaped separator and the negative electrode plate sandwiched between the folded sheet-shaped separator may be stacked, or one of the positive electrode plate and the negative electrode plate may be sandwiched between the folded sheet-shaped separator and stacked with the other electrode plate. Also, the sheet-shaped separator may be folded into an accordion shape, and the positive electrode plate and the negative electrode plate may be sandwiched between the accordion-shaped separator so that the separator is interposed between them. When a bag-shaped separator is used, the bag-shaped separator may house the positive electrode plate or the negative electrode plate.
[0145] (electrolyte) The electrolytic solution is an aqueous solution containing sulfuric acid, which may be gelled as necessary. The electrolytic solution may contain the above-mentioned polymer compound (P).
[0146] The electrolytic solution may contain cations (e.g., metal cations) and / or anions (e.g., anions other than sulfate anions (e.g., phosphate ions)) as necessary. Examples of metal cations include at least one selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.
[0147] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. is, for example, 1.20 or more, and may be 1.25 or more. The specific gravity of the electrolyte at 20° C. is 1.35 or less, and preferably 1.32 or less.
[0148] The specific gravity of the electrolyte at 20° C. may be 1.20 or more and 1.35 or less, 1.20 or more and 1.32 or less, 1.25 or more and 1.35 or less, or 1.25 or more and 1.32 or less.
[0149] (others) The lead-acid battery can be obtained by a manufacturing method including a step of housing a plate group and an electrolyte in a cell chamber of a battery case. Each cell of the lead-acid battery includes a plate group and an electrolyte housed in each cell chamber. The plate group is assembled by stacking a positive electrode plate, a negative electrode plate, and a separator such that the separator is interposed between the positive electrode plate and the negative electrode plate prior to housing in the cell chamber. The positive electrode plate, the negative electrode plate, the electrolyte, and the separator are each prepared prior to assembling the plate group. The manufacturing method of the lead-acid battery may include a step of chemically forming at least one of the positive electrode plate and the negative electrode plate, as necessary, after the step of housing the plate group and the electrolyte in the cell chamber.
[0150] The number of electrode plates in the electrode plate group may be one, or two or more.
[0151] An example of a lead-acid battery according to an embodiment of the present invention will be described below with reference to the drawings. The above description can be applied to the embodiment described below. The embodiment described below may be modified based on the above description. The matters described below may be applied to the above embodiment. Among the matters described below, matters that are not essential to the present invention may be omitted.
[0152] FIG. 1 shows an external view of an example of a lead-acid battery according to an embodiment of the present invention. The lead-acid battery 1 includes a battery case 12 that contains a plate group 11 and an electrolyte (not shown). The inside of the battery case 12 is divided into a plurality of cell chambers 14 by partition walls 13. Each cell chamber 14 contains one plate group 11. The opening of the battery case 12 is closed by a lid 15 that includes a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When rehydrating, the vent plug 18 is removed and rehydration liquid is replenished. The vent plug 18 may have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.
[0153] Each electrode plate group 11 is formed by stacking a plurality of negative electrode plates 2 and positive electrode plates 3 with a separator 4 interposed therebetween. Here, a pouch-shaped separator 4 that accommodates the negative electrode plates 2 is shown, but the shape of the separator is not particularly limited. In a cell chamber 14 located at one end of the battery case 12, a negative electrode shelf portion 6 that connects a plurality of negative electrode plates 2 in parallel is connected to a through connector 8, and a positive electrode shelf portion 5 that connects a plurality of positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 outside the lid 15. In a cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf portion 6, and a through connector 8 is connected to the positive electrode shelf portion 5. The negative electrode column 9 is connected to a negative electrode terminal 16 outside the lid 15. Each through connector 8 passes through a through hole provided in the partition wall 13 to connect the electrode plate groups 11 of adjacent cell chambers 14 in series.
[0154] The positive electrode shelf 5 is formed by welding the lugs provided on the upper part of each positive electrode plate 3 together by a cast-on-strap method or a burning method. The negative electrode shelf 6 is also formed by welding the lugs provided on the upper part of each negative electrode plate 2 together in the same manner as the positive electrode shelf 5.
[0155] The lid 15 of the lead-acid battery has a single structure (single lid), but is not limited to the illustrated example. The lid 15 may have a double structure including, for example, an inner lid and an outer lid (or a top lid). The lid having a double structure may have a reflux structure between the inner lid and the outer lid for returning the electrolyte to the inside of the battery (inside the inner lid) from a reflux port provided in the inner lid.
[0156] A lead-acid battery according to one aspect of the present invention will be described below.
[0157] (1) A lead-acid battery including a negative electrode including a negative electrode material and a positive electrode, The negative electrode material includes an organic shrinkage preventer and barium sulfate, The organic shrink-preventing agent is a condensation product containing a bisphenol unit, The surface area of the barium sulfate is 0.04 m2 or more per 1 g of the negative electrode material.
[0158] (2) In the above (1), the average particle size of the barium sulfate may be 0.5 μm or more and 1.0 μm or less.
[0159] (3) In the above (1) or (2), the content of the barium sulfate in the negative electrode material may be 0.9 mass % or more.
[0160] (4) In any one of the above (1) to (3), the organic shrink-preventing agent may be a condensation product containing a bisphenol S unit and a bisphenol A unit.
[0161] (5) In any one of the above (1) to (4), the negative electrode material may further contain a polymer compound other than the organic shrinkage inhibitor, and the content of the polymer compound in the negative electrode material may be in the range of 100 ppm to 1000 ppm by mass, and the polymer compound is measured using deuterated chloroform as a solvent. 1 In the chemical shift of the H-NMR spectrum, it may have a peak in the range of 3.2 ppm or more and 3.8 ppm or less.
[0162] (6) In any one of the above (1) to (4), the negative electrode material may further contain a polymer compound other than the organic shrinkage inhibitor, and the content of the polymer compound in the negative electrode material may be in the range of 100 ppm to 1000 ppm by mass, and the polymer compound may be oxy-C 2-4 It may contain alkylene units as a repeating structure.
[0163] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0164] 《Lead acid batteries A1~A10, C1~C6》 (1) Preparation of lead-acid batteries (a) Preparation of the negative electrode plate The raw materials lead powder, barium sulfate particles, carbon black, an organic shrinkage inhibitor, and optionally a polymer compound (P) are mixed with an appropriate amount of sulfuric acid aqueous solution to obtain a negative electrode paste. The negative electrode paste is then filled into the mesh of an expanded lattice made of a Pb-Ca-Sn alloy, and aged and dried to obtain an unformed negative electrode plate.
[0165] In the preparation of the negative electrode plates of the batteries C1 to C5, sodium lignin sulfonate (lignin compound) is used as the organic shrinkage preventer. In the preparation of the negative electrode plates of the batteries C6 and A1 to A10, an organic shrinkage preventer (B) is used as the organic shrinkage preventer. Specifically, a condensate of a bisphenol compound with a sulfonic acid group introduced therein and formaldehyde is used. As the polymer compound (P), polypropylene glycol (number average molecular weight is about 2000) is used. In the preparation of the negative electrode plates of the batteries C1 to C5, sodium lignin sulfonate is added to the negative electrode paste so that the content of sodium lignin sulfonate in the negative electrode material is 0.33 mass%. In the preparation of the negative electrode plates of the batteries C6 and A1 to A10, the organic shrinkage preventer (B) is added to the negative electrode paste so that the content of the organic shrinkage preventer (B) in the negative electrode material is 0.13 mass%. The barium sulfate particles and polymer compound (P) are added to the negative electrode paste so that the content in the negative electrode material is the content in Table 1. In addition, in the preparation of each negative electrode plate, carbon black is added to the negative electrode paste so that the content of carbon black in the negative electrode material is 0.9 mass%. The average particle size of the barium sulfate is changed by using commercially available barium sulfate particles with different average particle sizes. The surface area (Z) of barium sulfate per gram of negative electrode material can be changed by changing the amount of barium sulfate particles added to the negative electrode paste and / or the specific surface area of the particles.
[0166] (b) Preparation of the positive electrode plate The raw lead powder is mixed with an aqueous sulfuric acid solution to obtain a positive electrode paste, which is then filled into the mesh of an expanded lattice made of a Pb-Ca-Sn alloy, aged and dried to obtain an unformed positive electrode plate.
[0167] (c) Preparation of test battery The test battery has a rated voltage of 2V / cell and a rated 5-hour rate capacity of 32Ah. The plate assembly of the test battery consists of seven positive plates and seven negative plates. The negative plates are housed in a pouch-shaped separator made of a microporous polyethylene film and are stacked alternately with the positive plates to form a plate assembly. The plate assembly is housed in a polypropylene container together with an electrolyte (aqueous sulfuric acid solution) and chemically formed in the container to create a liquid-type lead-acid battery. The specific gravity of the electrolyte in a fully charged lead-acid battery at 20°C is 1.28.
[0168] (2) Evaluation (a) Evaluation of charging acceptance performance Using the fully charged test battery, a specified cumulative amount of electricity is measured. Specifically, the test battery is discharged at 6.4A for 30 minutes and left for 16 hours. After that, the test battery is discharged at 2.42V / cell. Determined The batteries are charged at a voltage (maximum current: 200A). The accumulated amount of electricity is measured for 10 seconds from the start of charging. All operations are carried out in a water tank at 25°C ± 2°C. The charge acceptance performance of each lead-acid battery is evaluated based on the ratio of the accumulated amount of electricity of each battery when the accumulated amount of electricity of lead-acid battery C1 is set to 100%.
[0169] (b) Evaluation of high-rate discharge performance at low temperatures after light load testing Using the lead-acid battery, a high-temperature light-load test is performed under the following conditions. Specifically, in order to create more overcharge conditions than the normal 4-10 minute test specified in JIS D5301, a charge-discharge cycle (1-10 minute test) consisting of 1 minute of discharge and 10 minutes of charge is performed at 75°C under the following conditions. A high-temperature light-load test in which this charge-discharge cycle is repeated 1220 times is performed using the lead-acid battery. Discharge: 25A, 1 minute Charging: 2.47V / cell, 25A, 10 minutes Water tank temperature: 75℃
[0170] The fully charged test battery after the high-temperature light-load test is discharged at a discharge current of 150A until the terminal voltage reaches 1.0V / cell at -15°C. The discharge time (s) at this time is used to evaluate the high-rate discharge performance at low temperature after the light-load test. The longer the discharge time, the better the low-temperature high-rate discharge performance. The low-temperature high-rate discharge performance of each battery is evaluated as a ratio (%) when the discharge time of the lead-acid battery C1 is set to 100.
[0171] Some of the production conditions and evaluation results are shown in Table 1. In Table 1, the surface area (Z) of barium sulfate is the surface area per 1 g of the negative electrode material. The contents of barium sulfate and polymer compound (P) are the contents based on mass in the negative electrode material.
[0172] [Table 1]
[0173] The higher the low-temperature high-rate discharge performance and charge acceptance in Table 1, the more preferable. The low-temperature high-rate discharge performance in Table 1 is preferably 100% or more, more preferably 105% or more, even more preferably 110% or more, and particularly preferably 115% or more. It is more preferable that the low-temperature high-rate discharge performance is 100% or more, and even more preferably that the charge acceptance is 115% or more. The charge acceptance in Table 1 is preferably 102% or more, more preferably 105% or more, even more preferably 110% or more, and particularly preferably 115% or more (e.g., 120% or more). Batteries having a low-temperature high-rate discharge performance of 100% or more and a charge acceptance of more than 102% are preferable.
[0174] As shown in Table 1, the batteries A1 to A10, which use the organic shrinkage inhibitor (B) as the organic shrinkage inhibitor and have an average particle size of barium sulfate of 0.04 μm or more (e.g., 0.05 μm or more), can achieve both high low-temperature high-rate discharge performance and high charge acceptance performance, unlike the batteries C1 to C6.
[0175] As shown in Table 1, all of the batteries A4 to A6 in which the polymer compound (P) was added to the negative electrode material exhibited high low-temperature high-rate discharge performance and high charge acceptance performance.
[0176] The evaluation results of the low-temperature high-rate discharge performance and the charge acceptance performance of the batteries C1 to C4 and the batteries C6 and A1 to A3 are shown in Figures 2 and 3, respectively. The organic condensation product of the batteries C1 to C4 is a lignin compound. The organic condensation product of the batteries C6 and A1 to A3 is the organic condensation product (B).
[0177] As shown in FIG. 2, as the surface area (Z) of barium sulfate increases, the high-rate discharge performance improves. This improvement is gradual in the battery using a lignin compound as the organic shrinkage preventer. On the other hand, in the battery using organic shrinkage preventer (B), the high-rate discharge performance increases when the surface area (Z) of barium sulfate is increased to 0.02 m. 2 / g (e.g., 0.04 m 2 / g or more or 0.05m 2 / g or more), the high rate discharge performance increases rapidly.
[0178] As shown in FIG. 3, in a battery using a lignin compound as an organic shrinkage preventer, the charge acceptance performance decreases slightly as the surface area (Z) of barium sulfate increases. On the other hand, in a battery using organic shrinkage preventer (B) as an organic shrinkage preventer, the charge acceptance performance improves as the surface area (Z) of barium sulfate increases. In a battery using organic shrinkage preventer (B), the charge acceptance performance increases when the surface area (Z) of barium sulfate increases to 0.02 m 2 / g (e.g., 0.04 m 2 / g or more or 0.05m 2 / g or more), the charge acceptance performance is greatly improved.
[0179] The reason why the above results were obtained is not clear at present, but it can be considered as follows. When the surface of barium sulfate is covered with an organic shrinkage preventer, the effect of adding barium sulfate is reduced. From various studies, it was found that the area covered by the organic shrinkage preventer (B) on the negative electrode active material or additives may be larger than the area covered by the same amount of lignin compound on the negative electrode active material or additives. Therefore, when using the organic shrinkage preventer (B) as the organic shrinkage preventer, it is considered necessary to add barium sulfate to the negative electrode material so that it has a surface area (Z) of a specified value or more.
[0180] To enhance the effect of making the surface area (Z) of barium sulfate equal to or greater than a predetermined value, the average particle size of barium sulfate is also important. By making the average particle size of barium sulfate smaller, the amount of barium sulfate required to be added can be reduced. Conversely, by making the average particle size of barium sulfate larger, it becomes easier to avoid problems such as barium sulfate blocking the pores of the negative electrode material and the negative electrode active material becoming less likely to bond together. Therefore, it is preferable to set the average particle size of barium sulfate within a predetermined range. [Industrial Applicability]
[0181] The present invention can be used for lead-acid batteries. The lead-acid battery of the present invention is suitable for use in idling-stop vehicles as an IS lead-acid battery that is charged and discharged under PSOC conditions. The lead-acid battery can also be suitably used as a starting power source for vehicles (such as automobiles and motorcycles) and industrial power storage devices (such as power sources for electric vehicles (such as forklifts)). These uses are merely examples and are not limited to these uses. [Explanation of symbols]
[0182] 1:Lead acid battery 2: Negative plate 3: Positive plate 4: Separator 5: Positive electrode shelf 6: Negative electrode shelf 7: Positive pole 8: Through connector 9: Negative pole 11: Plate group 12:Battery container 13: Bulkhead 14: Cell Room 15: Lid 16: Negative terminal 17: Positive terminal 18: Liquid outlet plug
Claims
1. A lead-acid battery including a negative electrode including a negative electrode material and a positive electrode, The negative electrode material includes an organic shrinkage preventer and barium sulfate, The organic shrink-preventing agent is a condensation product containing a bisphenol unit, The surface area of the barium sulfate is 0.04 m per 1 g of the negative electrode material. 2 That's all. The content of the barium sulfate in the negative electrode material is 0.9% by mass or more, The negative electrode material further includes a polymer compound other than the organic shrinkage inhibitor, The content of the polymer compound in the negative electrode material is in the range of 100 ppm to 1000 ppm by mass, The lead-acid battery, wherein the polymer compound has a peak in the range of 3.2 ppm or more and 3.8 ppm or less in a chemical shift of a 1 H-NMR spectrum measured using deuterated chloroform as a solvent.
2. A lead-acid battery including a negative electrode including a negative electrode material and a positive electrode, The negative electrode material includes an organic shrinkage preventer and barium sulfate, The organic shrink-preventing agent is a condensation product containing a bisphenol unit, The surface area of the barium sulfate is 0.04 m per 1 g of the negative electrode material. 2 That's all. The content of the barium sulfate in the negative electrode material is 0.9% by mass or more, The negative electrode material further includes a polymer compound other than the organic shrinkage inhibitor, The content of the polymer compound in the negative electrode material is in the range of 100 ppm to 1000 ppm by mass, The lead-acid battery, wherein the polymer compound contains an oxy-C 2-4 alkylene unit as a repeating structure.
3. 3. The lead acid battery according to claim 1, wherein the barium sulfate has an average particle size of 0.5 μm or more and 1.0 μm or less.
4. The lead acid battery according to any one of claims 1 to 3, wherein the organic shrinkage inhibitor is a condensate containing a bisphenol S unit and a bisphenol A unit.
Citation Information
Patent Citations
Lead-acid battery
JP1985182662A
Negative electrode plate for sealed lead-acid battery
JP1998040906A
Sealed type lead storage battery
JP2003036882A
Negative electrode plate for lead acid storage battery, and lead acid storage battery using the negative electrode plate
JP2012043594A
Evaluation method of lead storage battery
JP2018116842A